Information Literacy Training Program for librarians of the Integrated System of Libraries of the Federal University of São Carlos, Brazil - Maia, Cristina Marchetti; dos Santos, Camila Araújo [UNESP] (Universidad Nacional de La Plata, 2022)
The article presents the structuring and application of the Information Literacy Training Program for librarians of the Integrated System of Libraries of the Federal University of São Carlos, Brazil. The objective of the study was to analyze how the transversal steps of planning and mapping of information literacy at the institutional and educational levels were decisive for the design of training strategies. The Program consists of an action front focused on the professional improvement of the SIBi team and the other front focused on the development of events, activities and the creation of materials aimed at meeting the demands of the academic community. The research has a qualitative approach with a descriptive-exploratory nature. We use participant observation and the questionnaire to understand, holistically and in an integrated way, the object in focus. At first, the alignment of the program's activities with the Santos framework (2020) was reported, whose result of this intersectoriality culminated in the 1st CoInfo Training Cycle of the team's librarians. In a second moment, the entire Program was described based on the principles of the Action Plan of the International Federation of Library Associations and Institutions (2007), in which it was found that all the activities proposed in the Program corroborate the rise of transversal competences, a tendency advocated in the report International Federation of Library Associations and Institutions (2021). It is evident that institutional support is a differential, since the objectives of the program must be in line with those of the library so that librarians are sensitized about their participation and contribution to improving service to the community. It is hoped that the reported experience can serve as a guide for librarians to align, together with their institution's management and policy instances, training and updating actions for their knowledge on information literacy.
Programa de Formación en Alfabetización Informacional para bibliotecarios del Sistema Integrado de Bibliotecas de la Universidad Federal de São Carlos, Brasil
Programa de Formação de Competência em Informação para bibliotecários do Sistema Integrado de Bibliotecas da Universidade Federal de São Carlos, Brasil
Keywords: Brazil; Federal University of São Carlos; Information literacy; Librarians; Training program